Teachers' Perspectives in Arabic Education: A Narrative Inquiry from Pesantren Ar-Raudlatul Hasanah - Radinal Mukhtar Harahap; Rasyidin Rasyidin; Syarifah Sri Hidayah; Maimanah Samsuri (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2025)
Purpose – This study examines how Arabic language teachers at Pesantren Ar-Raudlatul Hasanah implement the Direct Method, focusing on their instructional strategies and the challenges they encounter. Design/methods/approach – Using a narrative inquiry approach grounded in Clandinin and Connelly’s framework, data were collected through unstructured narrative interviews with ten teachers (2–5 years’ experience), supported by observations and field notes. The narratives were thematically analyzed while preserving the authenticity of teachers’ voices. Findings – The results show that teachers employ a context-responsive hybrid Direct Method, combining full Arabic instruction with selective translation, peer clarification, embodied demonstration, teaching aids, and outdoor activities. Challenges include spelling accuracy, differing literacy backgrounds, large class sizes, and fluctuating student attention. Teachers respond through individualized support, repetitive drills, collaboration with senior tutors, and adaptive code-switching. Research implications – The study contributes the concept of a Pesantren-Based Hybrid Direct Method and highlights the value of narrative inquiry in uncovering teachers’ lived pedagogical reasoning. It recommends strengthening teacher training, improving media availability, and aligning assessment with oral–written balance.الهدف - يهدف هذا البحث إلى دراسة كيفية توظيف معلّمات اللغة العربية في معهد الروضة الحسنة للتربية الإسلامية بميدان لطريقة التدريس المباشرة، مع التركيز على إستراتيجياتهن التعليمية والتحديات التي يواجهنها. المنهج والمدخل والتصميم - استخدم البحث منهج الاستقصاء القصصي بالاعتماد على إطار كلاندينين وكونلي، حيث جُمعت البيانات عبر مقابلات سردية غير مقيَّدة مع عشر معلّمات يمتلكن خبرة تدريس تتراوح بين سنتين وخمس سنوات، إضافة إلى الملاحظات الميدانية. وحُلّلت السرديات موضوعيًا مع الحفاظ على أصالة صوت المبحوثات. النتائج - أظهرت النتائج أن المعلّمات يطبّقن صيغة هجينة من الطريقة المباشرة تجمع بين استخدام العربية الكاملة والترجمة الانتقائية، والتوضيح بين الطالبات، والتعليم الجسدي، والوسائل التعليمية، والأنشطة خارج الصف. وتتمثّل التحديات في ضعف الإملاء، وتباين الخلفيات القرائية، وكِبَرحجم الفصول، وتشتّت الانتباه. وقد واجهن هذه التحديات عبر الدعم الفردي، والتدريبات المتكررة، والتعاون مع المدرّسات الخبيرات، واستخدام التحويل اللغوي عند الحاجة. الآثار - يقدّم البحث إسهامًا مفاهيميًا يتمثّل في إبراز الطريقة المباشرة الهجينة في سياق المعهد، ويؤكد فاعلية المنهج السردي في الكشف عن منطق الممارسة لدى المعلّمات. وتوصي النتائج بتطوير برامج تدريب معلّمات اللغة العربية، وتوفير وسائل تعليمية أكثر تنوّعًا، ومواءمة أدوات التقييم بين المهارات الشفوية والكتابية.